2019
DOI: 10.12783/dtssehs/icssm2018/27081
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the U.S. Trade Policies in the Primary Products

Abstract: This study empirically analyzed the U.S. trade patterns of primary products. We used the H-index weighting to measure the degree of the U.S. trade policies in exports and imports. We find the U.S. has considerably encouraged the imports, and has slightly promoted the exports of primary products. We conclude that the agricultural subsidies, which help the U.S. economic growth and resource saving, are the major determinant for the export patterns of the U.S. primary products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Some previous studies employed RSCAX and (or) HX to analyze the patterns of the commodity exports (or imports) of China [14][15][16], Japan [17] and Korea [18], and conducted time series analyses [19] or panel co-integration analyses [20] as well as short-run and long-run Granger causality analyses. They found that most of the East Asian countries had adopted export promotion protectionism policies, while the United States had reversely imposed promotion policies in the import of primary products [21]. Consequently, the indicator of HX may be also applicable in the Indian export patterns in services.…”
Section: Indicator Of Export Promotion Degreementioning
confidence: 99%
“…Some previous studies employed RSCAX and (or) HX to analyze the patterns of the commodity exports (or imports) of China [14][15][16], Japan [17] and Korea [18], and conducted time series analyses [19] or panel co-integration analyses [20] as well as short-run and long-run Granger causality analyses. They found that most of the East Asian countries had adopted export promotion protectionism policies, while the United States had reversely imposed promotion policies in the import of primary products [21]. Consequently, the indicator of HX may be also applicable in the Indian export patterns in services.…”
Section: Indicator Of Export Promotion Degreementioning
confidence: 99%